1994
DOI: 10.1007/bf00024802
|View full text |Cite
|
Sign up to set email alerts
|

Thidiazuron-induced in vitro shoot formation from roots of intact seedlings of Albizzia julibrissin

Abstract: Seedlings of silktree (Albizzia julibrissin Durrazz .) were grown in vitro on MS-media containing B5 vitamins, 3% sucrose, 0.25% phytagel and various concentrations (0 .1-10 µM) of thidiazuron (TDZ) . Addition of TDZ to the culture medium greatly reduced shoot and root elongation but did not influence shoot production from the cotyledonary node or apex . Within 8-10 days the seedling roots split open, formed large masses of callus, and developed green patches which eventually grew into normal shoots while stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
1
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 14 publications
2
12
1
1
Order By: Relevance
“…About 50% of the control root explants formed shoot buds within 15 days after placement on B5 medium (Table 1). This is in sharp contrast to our previous results using intact seedlings (Sankhla et al, 1994) where no adventitious shoot formation occurred from roots in control cultures.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…About 50% of the control root explants formed shoot buds within 15 days after placement on B5 medium (Table 1). This is in sharp contrast to our previous results using intact seedlings (Sankhla et al, 1994) where no adventitious shoot formation occurred from roots in control cultures.…”
contrasting
confidence: 56%
“…Furthermore, we observed that higher concentrations of TDZ (0.1 and 1.0 #M) drastically inhibited the elongation of shoots formed on the excised roots. Thidiazuron has displayed many biological properties similar to purine cytokinins (Huetteman & Preece, 1993;Mok etal., 1987;Sankhla et al, 1994). In many cytokinin-dependent system TDZ exhibits a considerably higher degree of biological activity than purine-type cytokinins (Mok et al, 1987;Sankhla et al, 1994;Thomas & Katterman, t986) and is being evaluated for its morphogenic effects in several areas of tissue culture research (Gill & Saxena, 1993;Huetteman & Preece, 1993;Sankhla et al, 1994;Saxena et al, 1992).…”
mentioning
confidence: 99%
“…Various plants may need altered incubation periods for differentiation and morphogenesis. This is probably due to the capacity of TDZ in stimulating endogenous cytokinin biosynthesis or in altering cytokinin metabolism (Sankhla et al, 1994;Zhou et al, 1994). Therefore, it is suggested that double stage culture procedure consisting of culture of plant tissue on TDZmedium for appropriate period (usually 10 to 20 days) followed by a secondary TDZ-free medium, is beneficial for shoot proliferation and/or somatic embryogenesis.…”
Section: Effects Of Concentrationmentioning
confidence: 99%
“…This is not unique, a somewhat similar development occurred in cultures of other species. For example, seedling cultures of Albizzia julibrissin produced shoots from green nodules (Sankhla et al, 1994) and suspension cultures of Liriodendron tulipifera formed proembryogenic nodules that elongated into mature embryos (Merkle et al, 1993). Microspores and megagametophytes of Ginkgo biloba grew globules that developed into heart-or club-shaped embryos (Laurain et al, 1993a,b) while mature zygotic embryos of Sequoia sempervirens produced compact callus masses that generated somatic embryos, some of which germinated (Bourgkard and Favre, 1988).…”
Section: Discussionmentioning
confidence: 99%